If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18m+10=-12m-6
We move all terms to the left:
18m+10-(-12m-6)=0
We get rid of parentheses
18m+12m+6+10=0
We add all the numbers together, and all the variables
30m+16=0
We move all terms containing m to the left, all other terms to the right
30m=-16
m=-16/30
m=-8/15
| 2n-3=-9-4n | | 2x-4/8=4x | | 18m+10=-11m-6 | | 4x/3-x=x/1 | | 2(a+7)=4 | | 5x+5+3x=105 | | 29−31+x=-35 | | 210.5=10(3p+2) | | 14x+16+6x=-8(3-2x) | | 1/4(5/11-2x)-6/11=10/11 | | 25x-10(x-5)=14x+74 | | 2c+4c=-18 | | 9x-1+2x-2=2 | | 7=-5+x | | 5k-6=-106 | | 93.6+k=14.8 | | 3(x+10)=34-x | | 1/4(4/9-3x)-8/9=6/9 | | 6j=80 | | 0.25t^2+20t=10000 | | e/4+10=-8 | | 4+5m=6 | | 3(x+5)=2(-6-x) | | 4(5+2x)-5=3(3x+7 | | 0.11p=1.01 | | 3/4x-10=1 | | x^2-20x+72=0 | | 7w-14=-14-3w | | 3150=(-9.8+278x)(1.44927363) | | 2x×10=60 | | 7n+29=42n+22 | | 3y-10=5y-24 |